Micromobility and financial capital: the case of Tembici (Itaú Bank) in the city of São Paulo, Brazil - Leandro Di Genova Barberio; Fernando Guilherme Silveira Manocchio; Fabrício Gallo (Geografares, 2023)
The financialization process and information technologies have driven market development in different sectors of society. Urban mobility is one of the urban sectors that has been most impacted. This paper aims to discuss the concept of micromobility and how financial institutions operate in this sector in the city of São Paulo (SP), highlighting the case of Tembici (Itaú Bank). The methodology adopted includes a bibliographic review of national and international scientific productions, both primary and secondary, and qualitative and quantitative data, collected through fieldwork and reports. We sought to interpret the territorial impacts of specific digital platforms, examining different uses of the territory, and analyzing how this company promotes the expansion of mobility services. The results reveal how urban space, driven by the use of technology by financial institutions, becomes a profitable market that directly affects urban mobility.